Viscosity profile of Eucheuma spinosum carrageenan from Nusa Penida (Bali), Sumenep (Madura), and Takalar (Sulawesi Selatan) - Andarini Diharm Diharmi; Dedi Fardiaz; Nuri Andarwulan; Endang Sri Heruwati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
The research was conducted to determine the viscosity profile of carrageenan solution obtained from three different coastal region of Nusa Penida, Sumenep, and Takalar as a result of a decrease in temperature with presence cations K+ and Ca2+. Carrageenan was extracted from Eucheuma spinosum using hot alkaline calcium hydroxide Ca(OH)2 at 95°C, pH was decreased with HCl, carrageenan was precipitated with ethanol, dried and grinded. The viscosity profile of carrageenan was determined by addition of K+ (0.005-0.03% KCl) and Ca2+ (0.005-0.02% CaCl2)using a Rapid Visco Analyser (RVA). The viscosity profile of carrageenan solution changed upon cooling started from a dilute at the initial temperature of 80°C, and then increased as temperature decreased to 20°C. The viscosity of carrageenan E. spinosum from Nusa Penida, Sumenep, and Takalar without the addition of K+ and Ca2+ at a temperature of 80°C respectively were 90, 120, and 130 mPa.s. The viscosity of carrageenan from Nusa Penida, Sumenep, and Takalar in the presence of K+ and Ca2+ increased with increasing time and decreasing temperature. The viscosity of carrageenan from Nusa Penida in the presence of K+ (0.005-0.03% KCl) at 55oC becomes 125, 250, 300 mPa.s, Sumenep 280, 290, and 360 mPa.s, and Takalar 420, 420, and 420 mPa.s. While, in the presence of Ca2+ (0.01-0.02% % CaCl2) at 55oC, the viscosity of carrageenan from Nusa Penida, Sumenep, and Takalar have been formed gelling. Increasing of viscosity of carrageenan from Nusa Penida, Sumenep, and Takalar in the presence of kation Ca2+ was required a faster time and higher temperatures than K+. Carrageenan solution from E. spinosum originated from different coastal regions showed different viscosity profiles.Keywords: Eucheuma spinosum, carrageenan, cation, temperature, viscosity profile